El espacio controlado de experimentación en el sector de telecomunicaciones: ¿otro caso de mimetismo isomórfico en el derecho administrativo de América Latina? - Hernández González, José Ignacio (2025)
The Latin American administrative promoted the institutional borrowing of the regulation, proposing recently with the transposition of ‘regulatory sandboxes’ or regulatory testing spaces. This borrowing generates the risk of focusing on the form rather than the substance of these spaces, whose effective implementation requires changing paradigms of administrative law centered on the administrative power. Legislative Decree 1599 faces this risk, introducing controlled spaces to promote technological innovation and to the gap in access to telecommunications services. This article proposes two interpretation techniques to improve efficiency in implementing this space: interpreting the Decree from traditional institutions of economic administrative law, such as the authorization technique, but shifting traditional paradigms to interpret the Decree to facilitate experimentation and innovation.